UCEC STRESSES ON IMPORTANCE OF KNOWLEDGETRANSFER PARTNERSHIP (KTP) - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
GOLD COAST, AUSTRALIA, 3 November 2013 – Knowledgetransfer partnership (KTP) is important in promoting the transfer of knowledge through the exchange of creative and innovative ideas, experiences and skills, between universities and the community at large.